ASSESSMENT OF THE 187RE DECAY CONSTANT BY CROSS CALIBRATION OF RE-OS MOLYBDENITE AND U-PB ZIRCON CHRONOMETERS IN MAGMATIC ORE SYSTEMS - Selby D.; Creaser R.A.; Stein H.J.; Markey R.J.; Hannah J.L. (My University, 2007)
The past decade has seen renewed interest in 187Re-187Os geochronology using a variety of matrices including sulfide minerals, shales and meteorites. The most widely used value of the 187Re decay constant (λ 187Re) is 1.666 ± 0.005 × 10-11 a-1 (±0.31%), which is based on cross calibration of Re-Os and Pb-Pb chronometers for certain meteorites [Smoliar M. I., Walker R. J., and Morgan J. W. (1996) Re-Os isotope constraints on the age of Group IIA, IIIA, IVA, and IVB iron meteorites. Science 271, 1099-1102]. However, other recent studies have yielded alternate values of λ 187Re, based upon either direct counting experiments or analysis of meteorites. Here, we provide an independent assessment of λ 187Re, using methodology, sample materials, and preparation of Os standard solutions different from those of Smoliar et al. (1996). Combining Re-Os age data for molybdenite formed in magmatic ore deposits, with the U-Pb zircon age of the magmatic rocks, a refined λ 187Re value is determined by averaging 11 individual cross-calibration experiments spanning ca. 2700 Ma of Earth history. Using the U decay constants of Jaffey [Jaffey A. H., Flynn K. F., Glendenin L. E., Bentley W. C., and Essling A. M. (1971) Precision measurement of half-lives and specific activities of 235U and 238U. Phys. Rev. 4, 1889-1906], a value for λ 187Re of 1.6668 ± 0.0034 × 10-11 a-1 is determined. Using the λ 238U value of Jaffey et al. (1971) and λ 235U value of Schoene [Schoene B., Crowley J. L., Condon D. J., Schmitz M. D., and Bowring S. A. (2006) Reassessing the uranium decay constants for geochronology using ID-TIMS U-Pb data. Geochim. Cosmochim. Acta 70, 426-445], a value for λ 187Re of 1.6689 ± 0.0031 × 10-11 a-1 is determined. These values are nominally higher (ca. 0.1 and ca. 0.2%) than the value determined by Smoliar et al. [Smoliar M. I., Walker R. J., and Morgan J. W. (1996) Re-Os isotope constraints on the age of Group IIA, IIIA, IVA, and IVB iron meteorites. Science 271, 1099-1102], but within calculated uncertainty. Further refinement of λ187Re by cross calibrating the molybdenite and U-Pb zircon chronometers should be possible by utilizing high precision, single-grain, chemical abrasion zircon U-Pb analyses. © 2007 Elsevier Ltd. All rights reserved.
Keywords: Re–Os molybdenite; U–Pb zircon